Development of Inter-Digital H-Mode Drift-Tube Linac Prototype With Alternative Phase Focusing for a Muon Linac in the J-PARC Muon G-2/EDM Experiment. (November 2019) - Nakazawa, Y.; Iinuma, H.; Iwata, Y.; Iwashita, Y.; Otani, M.; Kawamura, N.; Mibe, T.; Yamazaki, T.; Yoshida, M; Kitamura, R.; Kondo, Y.; Hasegawa, K.; et al.
Abstract: An inter-digital H-mode drift-tube linac (IH-DTL) is developed in a muon linac at the J-PARC E34 experiment. IH-DTL will accelerate muons from 0.34 MeV to 4.5 MeV at a drive frequency of 324 MHz. Since IH-DTL adopts an APF method, with which the beam is focused in the transverse direction using the RF field only, the proper beam matching of the phase-space distribution is required before the injection into the IH-DTL. Thus, an IH-DTL prototype was fabricated to evaluate the performance of the cavity and beam transmission. As a preparation of the high-power test, a test coupler is designed and fabricated. In this paper, the development of the coupler and the result of the low-power measurement will be presented.